8. Sınıf Kalıtım Ünitesinin Öğretilmesinde By Şifreleme Modelinin Öğrencilerin Akademik Başarılarına ve Tutumuna Etkisi - Yıldırım, Bekir (Muş Alparslan Üniversitesi, 2013)
In this research, the effects of BY enciphering method on 8th grade students’ academic achievements and attitudes were investigated. The study group involves 8th grade students in Ankara, Etimesgut. A random class of 8th grade was determined as experimental group, another class was determined as control group. In the experimental group, the genetics course was given by using the BY enciphering method. In the control group, the genetics course was given by using the concept cartoon. The analysis of the data is made with Arithmetical Medium, and by using t-test for each of dependent and independent groups. According to the statistics gathered according to the results of the analysis of the research, BY Enciphing Method practiced on the experiment group resulted in higher improvement in the success level of the students in Science Courses, compared to The Concept Cartoon that is practiced on the control group in the school. In terms of the students’ attitudes in experiment and control groups towards Science Courses, in the group practicing BY Enciphing methodology the attitudes towards Science Courses are developed in a positive direction, whereas in the control group, such a normal change and development is noticed

Bu Araştırmada, BY şifreleme modelinin 8. sınıf öğrencilerinin akademik başarılarına ve tutumlarına etkisi araştırılmıştır. Araştırmanın çalışma grubu, Ankara, Etimesgut’ta okuyan 8. sınıf öğrencileri oluşturmuştur. İlköğretim 8. sınıf şubelerinden rastgele seçilen bir sınıf deney grubu, diğer sınıf control grubu olarak belirlenmiştir. Deney grubunda kalıtım dersi BY şifreleme yöntemi ile işlenmiştir. Kontrol grubunda ise kavram karikatürü ile işlenmiştir. Verilerin analizi; aritmetik ortalama, bağımlı gruplar için t-testi ve bağımsız gruplar için t-testi kullanılarak yapılmıştır. Araştırmadan elde edilen bulgulara göre; fen bilgisi dersinde deney grubuna uygulanan BY şifreleme metodunun, kontrol grubuna uygulanan Kavram Karikatürlerine göre akademik başarı düzeylerini arttırmada daha etkili olduğu istatistikî olarak belirlenmiştir. Deney ve kontrol grubu öğrencilerinin fen bilgisine karşı tutumlarına bakıldığında; BY şifreleme yöntemi ile ders işleyen deney grubunun görüşlerinde olumlu yönde bir gelişme olduğu, kontrol grubunda ise normal bir değişiklik olduğu görülmüştür.
The Effects of By Enciphing Method on the Achievements, and Attitudes on Genetics Unit Learned By the 8th Grade Students
msufbd
Keywords: BY Enciphering Method; Concept Cartoon; Student Achievement; and Attitude; BY şifreleme modeli; Kavram Karikatürü; Öğrenci Başarısı ve Tutum